Does Reciprocity Affect Analysts’ Incentives to Release Timely Information? Evidence from Syndication Relationships in Securities Underwriting - Mao, Connie X.; Song, Wei-Ling (Management Science, 2021)
Reciprocity is a subtle but influential factor in maintaining business relationships. We examine the stock recommendations, earnings forecasts, and target prices issued by “reciprocity-pressured” analysts affiliated with securities underwriters who rely on other major underwriters’ invitations to be in syndicates. Consistent with the reciprocal pressure hypothesis, we find that reciprocity-pressured analysts delay releasing negative information on other major underwriters’ clients despite the fact that these analysts’ affiliated underwriters do not receive fees from those clients. We also document temporary retaliation by major underwriters when reciprocity-pressured analysts deviate from such expected reciprocity. The results suggest that reciprocal pressure in the investment banking industry has a real effect on analyst information dissemination. This paper was accepted by Suraj Srinivasan, accounting.